2010
DOI: 10.1080/19415531003616862
|View full text |Cite
|
Sign up to set email alerts
|

School‐based prevention: current status and future challenges

Abstract: The field of school-based prevention of behavioral problems and promotion of caring and competence has grown dramatically in the past decade. This article provides a brief summary of current progress in the field and a discussion of future challenges and directions in research and practice. The article presents four future directions for research in the field of school-based prevention and health promotion: building the science of implementation and sustainability, building greater integration between educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 92 publications
4
131
0
5
Order By: Relevance
“…If current policy directives are to situate initiatives to promote students' positive mental health (such as social and emotional education) in school classrooms, is it acceptable that teachers' and schools' capabilities for enacting that new curriculum are considered, by the teachers themselves, to be less than optimal? Current literature on the science of sustainability point out that new initiatives that are poorly valued and poorly implemented at the school level are likely to fail, either in the short term, or as time passes and start-up resources such as project officers and additional funding are withdrawn (e.g., Greenberg, 2010;Scheirer, 2005;ShediacRizkallah & Bone, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If current policy directives are to situate initiatives to promote students' positive mental health (such as social and emotional education) in school classrooms, is it acceptable that teachers' and schools' capabilities for enacting that new curriculum are considered, by the teachers themselves, to be less than optimal? Current literature on the science of sustainability point out that new initiatives that are poorly valued and poorly implemented at the school level are likely to fail, either in the short term, or as time passes and start-up resources such as project officers and additional funding are withdrawn (e.g., Greenberg, 2010;Scheirer, 2005;ShediacRizkallah & Bone, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that well-designed school-based programs that are well-implemented can have positive impacts on students' mental health (Adi, Killoran, Janmohamend, & Stewart-Brown, 2007;Greenberg, 2010;Weare & Nind, 2011). For example, a review by Wells, Barlow and Stewart-Brown (2003) identified evidence of effectiveness for programs that adopted a whole-school approach, were implemented continuously for more than a year, and were aimed at the promotion of mental health as opposed to the prevention of mental illness.…”
Section: Outcomes Of School-based Mental Health Promotion Initiativesmentioning
confidence: 99%
“…Personality psychologists, for instance, have pointed to a basic trait like agreeableness (i.e., the tendency to be likeable and harmonious in relation to others) as a major determinant of prosocial behavior (Caprara et al 2012;Graziano and Eisenberg 1997). Values related to self-transcendence, which emphasizes accepting others as equals and displaying concern for their welfare (i.e., universalism and benevolence), are also important motives for prosocial behaviors (e.g., Schwartz 2010).…”
Section: Theoretical Model and Program Backgroundmentioning
confidence: 99%
“…In viewing self-efficacy beliefs as knowledge structures able to drive and sustain prosocial behavior, we placed special emphasis on their effects in enabling children to build positive interpersonal relationships with their peers in the classroom context. In addition, we also evaluated the effects of the CEPIDEA program on participants' agreeableness because it can be conceived as the dispositional tendency that may predispose adolescents to behave prosocially (Caprara et al 2012;Graziano and Eisenberg 1997 In addition, we considered the decline in aggression as a relevant outcome one may expect from promoting prosocial behavior. As stated above, previous findings suggest that prosocial behavior may exert a positive role in mitigating the destructive consequences of aggression on adolescents' development (Kokko et al 2006).…”
Section: The Present Studymentioning
confidence: 99%
“…Schools are central in the lives of youths and families, can capitalise on the availability of children and youth, and have staff with the professional expertise to recognise and respond to the systemic and developmental nature of students' social and emotional needs (Greenberg, 2010;Pullmann et al, 2013;Weare and Gray, 2003).…”
Section: Introductionmentioning
confidence: 99%